Japanese management in sport organizations: Reality or theoretical fiction - Nešić Milan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
Modern management is characterized by specific generic context that represents the main developing potential of every organization, as well as the sporting one. Because of that, basic functions of management (planning, organising, leading and control) are under constant scrutiny of modern theories of management. Regardless of the historical order of their occurrence, no unique and generally accepted theory exists today. Especially in the context of the problematics that sport management deals with. They evolve, complement one another, and, sometimes, merge. The most commonly used approach is an eclectic one, as a combination of principles from different theories, which is characteristic of new theoretical approaches to management. Although two dominant sport-organizing models have surfaced in the field of sport - the European and American one, one still cannot explicitly speak about the authentic European or American model of sport management. Because of that, consideration and study of different modern management theories, as well as identification of possible 'points' of applicability, become a necessary process that contributes to the development and promotion of sport management theory (and practice). Two theories that this paper treats are Japanese management and 'Z' theory, as orientations for models potentially applicable in sport organizations.